Relevance and Standardization of In Vitro Antioxidant Assays: ABTS, DPPH, and Folin–Ciocalteu - Helena Abramovič; Blaž Grobin; Nataša Poklar Ulrih; Blaž Cigić (Journal of Chemistry)
Trolox, gallic acid, chlorogenic acid, caffeic acid, catechin, epigallocatechin gallate, and ascorbic acid are antioxidants used as standards for reaction with chromogenic radicals, 2,2-diphenyl-1-picrylhydrazyl (DPPH⋅) and 2,2′-azino-bis-3-ethylbenzotiazolin-6-sulfonic acid (ABTS⋅+), and Folin–Ciocalteu (FC) reagent. The number of exchanged electrons has been analyzed as function of method and solvent. A majority of compounds exchange more electrons in FC assay than in ABTS and DPPH assays. In reaction with chromogenic radicals, the largest number of electrons was exchanged in buffer (pH 7.4) and the lowest reactivity was in methanol (DPPH) and water (ABTS). At physiological pH, the number of exchanged electrons of polyphenols exceeded the number of OH groups, pointing to the important contribution of partially oxidized antioxidants, formed in the course of reaction, to the antioxidant potential. For Trolox, small impact on the number of exchanged electrons was observed, confirming that it is more suitable as a standard compound than the other antioxidants.